Impact of polypharmacy in older patients with type 2 diabetes in rural population in South India - Sanjeev Kumar Adepu,; Madhukar Sirasu,; Gudas Ravinder, (Asian Journal of Medical Sciences, 2022)
Background: The World Health Organization describes polypharmacy as a safe and efficient treatment that complies with evidence-based medicine and uses at least five different medications. Aims and Objectives: The aim of our study was to investigate the impact of polypharmacy in older patients with type 2 diabetes mellitus (T2DM) in rural population in South India. Materials and Methods: The study comprised a total of 100 patients, who were referred to the Government General Hospital, Nizamabad, between January 2020 and March 2022. The records of 50 randomly chosen non-diabetic patients who visited our hospital for other ailments were compared to those of the 50 T2DM patients. Results: In this study, a total of 100 patients were enrolled, out of which 62 were male (62%) and 38 were female (38%). The duration of diabetes was noted to be 0–5 years in 28 patients, 6–10 years in 52 patients and >10 years in 20 patients. In our study, we observed that more than five drugs were prescribed to 45 patients in the case group and only ten patients in the control group. Conclusion: Our study shows that older adults with diabetes have a high prevalence of polypharmacy and that this condition may have a significant impact on a number of health-related outcomes. Each patient should receive a customized course of treatment with the right number of medications for their particular ailment. The danger of side effects increases with the number of medications.